Smells like pirates - Selfors, Suzanne (Smells like dog, 2012)
"Homer thought membership in L.O.S.T., the mysterious Society of Legends, Objects, Secrets, and Treasures, would help him find pirate Rumpold Smeller's missing treasure. But when Homer's enemy, Lorelei, forms an evil organization called FOUND, Homer and Dog face an impossible decision: Work with Lorelei to find the prize once and for all, or abandon their lifelong quest to locate the treasure"--Provided by publisher.